The prospects of pulsar timing with new-generation radio telescopes and the Square Kilometre Array. (16th April 2018) - Stappers, B. W.; Keane, E. F.; Kramer, M.; Possenti, A.; Stairs, I. H.
Abstract : Pulsars are highly magnetized and rapidly rotating neutron stars. As they spin, the lighthouse-like beam of radio emission from their magnetic poles sweeps across the Earth with a regularity approaching that of the most precise clocks known. This precision combined with the extreme environments in which they are found, often in compact orbits with other neutron stars and white dwarfs, makes them excellent tools for studying gravity. Present and near-future pulsar surveys, especially those using the new generation of telescopes, will find more extreme binary systems and pulsars that are more precise 'clocks'. These telescopes will also greatly improve the precision to which we can measure the arrival times of the pulses. The Square Kilometre Array will revolutionize pulsar searches and timing precision. The increased number of sources will reveal rare sources, including possibly a pulsar–black hole binary, which can provide the most stringent tests of strong-field gravity. The improved timing precision will reveal new phenomena and also allow us to make a detection of gravitational waves in the nanohertz frequency regime. It is here where we expect to see the signature of the binary black holes that are formed as galaxies merge throughout cosmological history. This article is part of a discussion meeting issue 'The promises of gravitational-wave astronomy'.